Biomechanical Comparison of Fibertape Device vs Cannulated Screw for Ligamentous Lisfranc Injury in a Cadaveric Model. Issue 2 (April 2022) - Koroneos, Zachary; Manto, Kristen M.; Martinazzi, Brandon J.; Staub, Jacob; Mellen, James; Stauch, Chris M.; Bifano, Shawn M.; Lewis, Gregory; Aynardi, Michael C.
Category: Midfoot/Forefoot; Sports Introduction/Purpose: The preferred method of fixation for ligamentous Lisfranc injuries is controversial, with the traditional method being transarticular screws. Unfortunately, screw removal is often required leading surgeons to seek alternative fixation methods including fibertape constructs. The purpose of this biomechanical study is to compare transarticular screws to a fibertape construct under a spectrum of biomechanical loads. This controlled laboratory study involved evaluating the diastasis at three joints in the Lisfranc complex in matched pairs and creating 3D models for each loading stage to evaluate at the plantar, interosseous, and dorsal aspects of each bone. Methods: Eight matched pairs of lower extremity cadaveric specimens were fixed with either a fibertape construct with a supplemental intercuneiform limb, or two transarticular cannulated crossed-screws. The diastasis between bones was measured at three midfoot joints in the Lisfranc complex; the Lisfranc articulation, the 2nd tarsometatarsal joint, and the intercuneiform joint using a 3D coordinate digitizer. Measurements were obtained for the pre-injured, injured, and fixation under static loading at 50% donor bodyweight. Specimens then underwent stepwise increases in cyclic loading performed at 1 Hz and 100 cycles, at additional 100 N ground reaction force intervals from 100 N to 2000 N to simulate postoperative loading from the partial weightbearing stage to high-energy activities. CT scans were obtained for each specimen to create 3D models that allowed for plantar and interosseous diastasis measurements. Failure of fixation was defined as diastasis greater than 2 millimeters at the Lisfranc articulation (second-metatarsal - medial-cuneiform joint). Results: There were no significant differences detected between groups in the pre-injury, injury or fixation stage and therefore no notable differences between groups prior to surgery with different constructs. Specimens fixed with the fibertape construct demonstrated failure in 1 of 8 (12.5%) specimens during a cycle with a peak force of 2000 N. In contrast, 2 of 8 (25%) specimens fixed with screws failed at peak forces of 1000 N and 1400 N. There were no significant differences in diastasis detected at the Lisfranc articulation or the intercuneiform joint throughout all loading cycles. However, the fibertape construct showed higher non-failure in statistical predictions, and significantly less motion at the adjacent 2nd tarsometatarsal joint. Conclusion: This study displayed a high level of repeatability in our injury creation under fluoroscopy with a specific criteria to avoid disrupting any adjacent ligaments and a threshold measurement of injury. The fibertape construct with a supplemental intercuneiform limb seems to provide comparable biomechanical stability to transarticular screws. There were no significant differences detected throughout our loading protocol which exceeds loads performed in previous studies. Furthermore, in combination with not requiring removal, this construct may allow for physiologic loading potentially providing accelerated post- operative protocols.